2011
DOI: 10.1007/s00464-011-1634-0
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and long-term results after left pancreatectomy: a single-institution, non-randomized, comparative study between open and laparoscopic approach

Abstract: Laparoscopic left pancreatectomy is a safe procedure for benign and borderline tumors, with similar perioperative outcomes compared with the open procedure. In the long term, the laparoscopic approach is likely to be superior thanks to a more rapid resume of full-time activities and to the lower incidence of incisional hernias and exocrine insufficiency. Clearly, these results have yet to be confirmed in large, randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
(56 reference statements)
1
22
0
3
Order By: Relevance
“…Several retrospective, single-center and multicenter studies have compared the outcomes between LDP and open distal pancreatectomy (ODP) [2,3,28,42,[64][65][66][67][68][69][70][71][72][73][74]. They indicated the superiority of LDP regarding blood loss, postoperative complications, such as surgical site infections, the recovery of physical function, and postoperative hospital stay.…”
Section: Laparoscopic Operationsmentioning
confidence: 99%
“…Several retrospective, single-center and multicenter studies have compared the outcomes between LDP and open distal pancreatectomy (ODP) [2,3,28,42,[64][65][66][67][68][69][70][71][72][73][74]. They indicated the superiority of LDP regarding blood loss, postoperative complications, such as surgical site infections, the recovery of physical function, and postoperative hospital stay.…”
Section: Laparoscopic Operationsmentioning
confidence: 99%
“…Marangos et al [33] found that the 3-year survival [5] 6.4/8.8 a 0%/3% 25%/41% 0%/7% 18%/20% 3.2/4.3 a 37%/45% 6%/7% N/A Soh et al [6] 5 [7] 8/9 0 48.2/45.2% 9.3%/9.6% 29.7%/13.7% 3.9/4.0 4.7%/2.7% N/A N/A Cho et al [8] 16%/54% (> 7d) 0.5%/1% 12%/15% 1%/3% 23%/27% 40%/58% (> 3.5 cm)…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…As a result, the application of laparoscopy to pancreatectomy has been slower compared to other abdominal procedures. As surgeons become more adept at advanced laparoscopy, there is increasing evidence demonstrating not only the safety and feasibility of laparoscopic pancreatic [3] 42/76 27.3/26.5 NS 35.7%/22.4% 304/281 375/375 11.9% Mehta et al [4] 30/30 N/A N/A 70%/30% a 188/226 294/729 a N/A Limongelli et al [5] 16/29 26.4/27.1 NS 31%/14% 204/160 a 160/365 a 6.0% Soh et al [6] 10/21 25/21 NS N/A 383/330 275/600 a N/A Butturini et al [7] 43/73 N/A N/A 44.2%/11% a 180/180 N/A 0.0% Cho et al [8] 254/439 NS NS 34%/10% a NS 24%/54% (> 300cc) 9.4% Aly et al [9] 40/35 21/21 N/A 32%/8% a 342/250 a 363/606 a 10.0% DiNorcia et al [10] 71/192 N/A NS 15.5%/15.6% 250/270 a 150/900 a 25.3% Jayaraman et al [11] 107/236 27/27 N/A 21%/14% 194/163 a 150/350 a 30.0% Kooby et al [12] 23/189 28.5/26.2 NS N/A 238/230 422/790 a 17.0% Vijan et al [13] 100/100 27.4/27.9 NS 25%/N/A 214/208 171/519 a 4.0% Baker et al [14] 27/85 N/A NS N/A 236/253 219.4/612.6 a 3.6% Finan et al [15] 44/104 28.3/26.9 NS 2%/2.7% 156/200 a 157/719 a 4.1% Nakamura et al [16] 21 [17] 7/4 29.5/29 N/A 100%/100% 182/152 214/362 0.0% Eom et al [18] 31 [19] 93 [20] 14/19 N/A NS N/A 290.7/213.8 a 247.1/400.3 7.0% Misawa et al [21] 8/9 N/A N/A 12.5%/0% 255/205 14/307 a 0.0% Tang et al [22] 9/5 N/A NS 55.6%/0% 180/210 100/450 a 0.0% Teh et al [23] 12 [24] 15/15 N/A N/A 0%/0% N/A N/A 20.0% Fernández-Cruz et al [25] 5/41…”
Section: Introductionmentioning
confidence: 99%
“…Barlett [29] and Butturini [30] works instead do not agree with the utility of LDP for PC treatment. Whereas the first articles underlines the excessive operative time, explaining that this result was because of the few cases they studied, concluding that this technique should be practiced by expert surgeons; instead the second article doubts about the utility of LDP for malignant cancers, as the anatomic structure of pancreas would not allow to eradicate the tumors fully as they would be too extended.…”
Section: Resultsmentioning
confidence: 91%